SEM Model of OTA PayLater Reuse Intention Through Trust : Model SEM Pada Niat Penggunaan Ulang Layanan OTA PayLater Melalui Kepercayaan - Ema Rosary Sitorus; Minto Waluyo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Buy Now Pay Later (BNPL) services integrated into Online Travel Agent (OTA) platforms have experienced rapid growth, particularly among Millennials and Generation Z, reflecting evolving digital financial behavior. Specific Background: Despite increasing adoption, OTA PayLater services encounter challenges related to service quality, promotion, risk perception, and user satisfaction, which shape trust and reuse intention. Knowledge Gap: Prior studies report inconsistent findings regarding the relationships among service quality, risk perception, promotion, user satisfaction, trust, and reuse intention, and limited research simultaneously examines these variables within the OTA PayLater context using trust as a mediating construct. Aims: This study analyzes the relationships between service quality, risk perception, promotion, and user satisfaction on trust and reuse intention toward OTA PayLater services. Results: Using a quantitative cross-sectional design and Structural Equation Modeling with Maximum Likelihood estimation on 120 respondents, the findings indicate that service quality, promotion, and user satisfaction significantly affect trust, while risk perception is not significant. Furthermore, service quality, user satisfaction, and trust significantly affect reuse intention, with trust demonstrating the strongest relationship. Novelty: This research integrates four antecedent variables within a single SEM framework in the OTA PayLater setting and empirically positions trust as a central determinant of continued usage. Implications: The results underscore the strategic importance of stable systems, transparent processes, responsive service, and sustained trust-building initiatives to support continued adoption of OTA PayLater services. Highlights: Trust shows the strongest positive relationship with continued usage decisions. Perceived risk does not demonstrate statistical significance in predicting behavioral outcomes. Customer satisfaction contributes to loyalty behavior alongside system reliability factors. Keywords: OTA PayLater, Service Quality, Trust, Reuse Intention, Structural Equation Modeling